DESIGN AND CONSTRUCTION OF WEBSITE CARBON CREDIT RECORDING APPLICATION - Muhammad Muhaimin Nur; Andi Hutami Endang (Program Studi Teknik Komputer, 2024)
Global climate change is caused by the increasing emissions of greenhouse gases, especially CO2, which have significant impacts on human-induced climate change. In addressing this issue, Indonesia is committed to reducing greenhouse gas emissions by 29% by 2030. The development of a carbon accounting system using the SDLC method in this research is an essential step towards achieving this target. This system helps companies to effectively reduce and report carbon emissions, supports transparency, and facilitates interaction among various stakeholders. Through research methods such as interviews, surveys, and the SDLC Waterfall method, the carbon accounting system can be implemented as an effective tool in managing carbon data, reducing emissions, and improving environmental quality.